Pendekatan Berbasis Pelanggan dalam Manajemen Mutu Pendidikan: Studi Kasus Sekolah Dasar Negeri 001 Muara Badak - Restiawati, Yanti; Azainil, Azainil (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study examines the implementation of a customer-based approach in education quality management at Sekolah Dasar Negeri 001 Muara Badak. Employing a qualitative research approach, this investigation seeks to identify implementation strategies, measure customer satisfaction levels, assess the impact on education quality, and identify constraints and challenges faced. Findings indicate that adopting a customer-oriented strategy effectively enhanced the standard of educational offerings and increased contentment among learners, their families, and educators. The school successfully integrated this approach through active stakeholder involvement in the education quality improvement process, including facility improvements and teacher training program development.